On Latin American and African Philosophy: History, Topics and Issues - Harris , Chad; Bavaresco, Agemir (Revista de Filosofía, 2021)
In this article we compare and contrast Latin American Philosophy and African Philosophy in terms of history, currents and themes. We present an overview of both philosophical traditions in which we describe the methodologies and movements associated with each tradition respectively. We end by suggesting potential areas for further collaboration between the two traditions based on the similarities and differences suggested by our presentation.